Anthraquinone-type inhibitor of α-glucosidase enhances glucose uptake by activating an insulin-like signaling pathway in C2C12 myotubes. (July 2019) - Alam, Md Badrul; Bajpai, Vivek K.; Ra, Jeong-Sic; Lim, Ji-Young; An, Hongyan; Shukla, Shruti; Quan, Khong Trong; Khan, Imran; Huh, Yun Suk; Han, Young-Kyu; Na, MinKyun; Lee, Sang-Han
Abstract: This study assesses the ability of anthraquinone derivative, 2-methyl-1, 3, 6-trihydroxy-9, 10-anthraquinone (MTAQ) to decrease postprandial hyperglycemia or enhance glucose uptake and to elucidate the underlying molecular mechanism. We investigated α-glucosidase inhibition, glucose uptake, and translocation of glucose transporter 4 (GLUT4) in C2C12 myotubes. The data indicate that MTAQ strongly inhibited α-glucosidase activity in a concentration-dependent manner, with an IC50 value of 6.49 ± 1.31 μM, and functioned as a reversible competitive inhibitor, with a dissociation constant of 41.88 μM. Moreover, MTAQ significantly augmented basal and insulin-stimulated glucose uptake as well as translocation of GLUT4 to the plasma membrane. It also stimulated the phosphorylation of insulin receptor β isoform, insulin receptor substrate-1, 3-phosphoinositide-dependent protein kinase 1, and protein kinase B (AKT). A pretreatment with an AKT inhibitor, LY294002, attenuated the ability of MTAQ to activate an insulin-like signaling pathway and to enhance basal and insulin-stimulated glucose uptake and stimulate GLUT4 translocation to the plasma membrane. These findings reveal the fact that MTAQ may have potential for the development of new antidiabetic drugs to manage blood glucose levels.